PERSEPSI MASYARAKAT TENTANG DOI’ MENRE DALAM PERNIKAHAN SUKU BUGIS DI KELURAHAN SIDODADI KECAMATAN WONOMULYO KABUPATEN POLEWALI MANDAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to determine how Doi’ Menre in Community Perception in Sidodadi Village, Wonomulyo District, Polewali Mandar Regency and how the meaning of doi' is translated into Bugis marriage, especially in Sidodadi Village, Wonomulyo District, Polewali Mandar Regency. The results of this research give rise to the perception or view of the public that thinks that doi 'menre is indeed very important and has become a habit that cannot be eliminated because the money given will be used to finance all organizational needs. Wedding ceremonies, considering daily necessities are getting more expensive, but there are also those who think that asking for instructions that are too high is an act of waste and increasing showing off, it would be nice if the money is used as business capital for the future to be useful. Doi 'Menre is a requirement of customary law that must be fulfilled, the high or low number of doi' which depends on the result of the agreement between the two parties of the family who will conduct the marriage. Marriage is the Sunnah of the Prophet, so make it easy and hope for the blessings and blessings of Allah SWT.